Persepsi dan penerimaan vaksin Covid-19 di kalangan wanita hamil dan menyusui - Wulandari, Setyo Retno; Andika, I Putu Juni; Istichomah, Istichomah; Ambarwati, Eny Retna (Jurnal Kesehatan Samodra Ilmu (JKSI), 2022)
Background : : Vaccination is critical in controlling the coronavirus disease 19 (COVID-19) pandemic. However, vaccine perception and acceptance among pregnant and lactating women is unknown. We aimed to determine the acceptance of COVID-19 vaccination among these two groups of women in Singapore, and factors associated with vaccine acceptance. We aimed to determine the acceptance of COVID-19 vaccination among these two groups of women, and factors associated with vaccine acceptance.Research methods : This library review uses a database with the electronic search on, Google Scholar, and ScienceDirect published in 2016 - 2021. Ten articles were used for review. The article discusses the perception and acceptance of the COVID-19 vaccine among pregnant and lactating women. Results and discussion : The conclution is Good perception and acceptance can speed up the COVID-19 vaccination process and emphasize the incidence in pregnant and lactating women.